Pengembangan Media Video Tutorial Membuat Sulaman Burci Bentuk Rumbai Pada Elemen Desain Hiasan Di SMKN 1 Jabon - Nabilatus Sholihah; Urip Wahyuningsih; Imami Arum Tri Rahayu; Ma'rifatun Nashikhah (Jurnal Bintang Pendidikan Indonesia, 2024)
This research aims to determine the feasibility of burci embroidery material through video tutorials. The type of research used is the type of research and development (R & D) with the ADDIE model to make the development of burci embroidery video tutorial media. Based on the results of development research and discussions that have been carried out, it can be concluded that the feasibility of video tutorial media on the technique of making tassel burci embroidery on decorative design elements obtained an average result of 91,8% with very decent categories by media experts and material experts.